Handbook of African American health social and behavioral interventions - Lemelle, Anthony J.; Reed, Wornie; Taylor, Sandra; SpringerLink (Online service). (New York, NY Springer New York, 2011)
The U.S. Census Bureau reports particular demographic, social, and health conditions for African Americans. Population-wide, the African American community has a higher mortality rate from cancer and diabetes than the rest of the population, a higher infant mortality rate, and a lower vaccination rate for influenza and pneumonia. The contributions to this comprehensive Handbook of African American Health uncover the specific demographic conditions of the African American population, and outline social interventions for both physical and mental health at the primary, secondary, and tertiary levels. The 26 contributions to this comprehensive volume cover interventions for a diverse range of health problems, including: obesity and cardiovascular disease; diabetes; asthma and other respiratory diseases; smoking, alcohol, and recreational drug abuse; risky sexual behaviors; cancer screening, prevention, and survivorship; infant mortality; community and interpersonal violence; mental health. From a healthcare standpoint, it also examines specific interventions for treatment compliance, health care access, and community collaborations. This volume will be an invaluable resource for researchers in medical sociology, mental health studies, public health, health behavior, and African American studies.
Part I Background of Social and Behavioral Health Disparities Interventions Among African Americans.- 1. Conceptual, Operational, and Theoretical Overview of African American Health Related Disparities for Social and Behavioral Interventions. Anthony J. Lemelle.- 2. Ethics and Intervention Programming. Cynthia Hudley.- Part II Fundamental Intervention Needs.- 3. Health, Nutrition, Access to Healthy Food and Well-Being Among African Americans. Angela J. Hattery and Earl Smith.- 4. Promoting Physical Activity in Black Children and Adolescents: Intervention Strategies Health Practitioners Have Put into Play. Raegan A. Tuff and Billy Hawkins.- Part III Major Lifestyle Intervention Considerations.- 5. Reducing Tobacco-Related Health Disparities: Using Mass Media Campaigns to Prevent Smoking and Increase Cessation in Underserved Populations. Jane A. Allen, Donna M. Vallone, and Amanda K. Richardson.- Part IV Important Interventions for Children.- 6. Preventing Childhood Lead Poisoning. Wornie Reed.- 7. Contemporary Interventions to Prevent and Reduce Community Violence Among African American Youth Duane E. Thomas, Elizabeth M. Woodburn, Celine I. Thompson, and Stephen S. Leff.
Electronic reproduction.
Keywords: African Americans -- Medical care -- Handbooks, manuals, etc; African Americans -- Health and hygiene -- Handbooks, manuals, etc; Electronic books